Dynamic Responses of Outer Radiation Belt Electron Phase Space Densities to Geomagnetic Storms: A Statistical Analysis Based on Van Allen Probes Observations - Xiaoyu Wang; Binbin Ni; Xing Cao; Xin Ma; Yuan Lei; Xiankang Dou (Space Weather)
Abstract Using Van Allen Probes observations from September 2012 to June 2019, we statistically investigate responses of the Earth's outer radiation belt electron phase space densities (PSDs) in the adiabatic invariant coordinates to isolated geomagnetic storms. Electron PSDs for μ = 50–5,000 MeV/G, covering energy range of seed, relativistic and ultra‐relativistic electrons, are calculated to evaluate three types of storm‐time PSD responses (i.e., enhancement, depletion, and no change). In statistics, the seed PSD variations are dominated by enhancement‐type events, the percentages of which increase from >50% for small storms (−50 nT < SYM‐Hmin ≤ −30 nT) to >70% for large storms (SYM‐Hmin ≤ −50 nT). The relativistic and ultra‐relativistic PSDs exhibit the three response types with comparable occurrence rates for small storms but present predominantly enhancement‐type variations (>50%) for large storms. Enhanced storm activity increases the enhancement‐type responses for seed PSDs at all L* and for relativistic and ultra‐relativistic PSDs at L* > 3.5. It also results in the increased depletion‐type response occurrence for relativistic and ultra‐relativistic PSDs at lower L*. Our results further indicate that the depletion‐type responses manifest evident dependence on the level of solar and geomagnetic activity and the μ‐value, implying complex physics accounting for outer zone electron losses. Improved knowledge of the storm‐time dynamics of outer radiation belt electron PSDs is valuable to in‐depth comprehension of various mechanisms responsible for the electron acceleration and loss. It has important implications for future simulations and forecasts of radiation belt electron variability, in particular, during geomagnetically disturbed periods.